Clinical evaluation of omega-3 fatty acids in psoriasis - Adil, Mohammad; Singh, Pramod Kumar; Maheshwari, Kopal (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Omega-3 fatty acids are largely derived from fish oils and are known to decrease inflammation. There have been a few small studies showing the beneficial effect of omega-3 fatty acids in psoriasis. Objective. To evaluate the efficacy of omega-3 fatty acids in conjunction with emollients in patients with mild to moderate chronic plaque psoriasis. Materials and methods . A total of 200 clinically diagnosed cases of chronic plaque psoriasis with less than 10% of body surface area involvement were recruited and divided into group A and group B. Group A was given 1,800 mg daily of omega-3 fatty acids in three divided oral doses and topical paraffin over the lesions. Group B was prescribed only topical paraffin. At the end of 12 weeks, treatment response was assessed by means of Psoriasis Area Severity Index (PASI), and by its components including area involved, erythema, induration and desquamation scores. Results. The mean PASI score changed from 7.44 to 3.96 in group A, and from 7.24 to 5.19 in group B. There was a statistically significant difference in PASI, erythema, induration, desquamation scores and area involved between the two groups after 12 weeks. Forty four (46.3%) patients in group A and 13 (13.9%) patients in group B achieved a 50% or more reduction in PASI scores. Conclusions . Omega-3 fatty acids in conjunction with topical emollients appear to reduce the severity of psoriasis with no major side effects. The combination can be a useful adjunct to other psoriasis treatments.